Protecting industrial control systems from electronic threats - Weiss, Joseph, ....- (New York : Momentum, 2010)
This book is meant to help both the novice and expert in Information Technology (IT) security and industrial control systems (ICS) gain a better understanding of protecting ICSs from electronic threats. The term "ICS" was chosen as ICSs include Supervisor